2018
DOI: 10.1136/bmjopen-2018-023302
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone use and Parkinson’s disease: a retrospective cohort study in Taiwan

Abstract: ObjectivesMany researchers have expected pioglitazone to serve as an effective neuroprotective agent against Parkinson’s disease (PD). Therefore, we conducted this cohort study to investigate the association between pioglitazone use and PD by using a large Asian population-based dataset in Taiwan.DesignRetrospective cohort study.SettingTaiwan.Participants7906 patients with diabetes who had received pioglitazone were defined as the study cohort, and 7906 matched patients with diabetes who had not received piogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…It also mitigates the reduction of DA in striatum of rotenone-treated rats [ 259 ]. However, a population-based study does not find the relationship between pioglitazone use and PD incidence among diabetic patients [ 260 ]. A randomized, double-blind, placebo-controlled trial of pioglitazone (15 or 45 mg/day) on 210 PD patients could not show a difference of UPDRS scores between treatment and placebo groups ( Table 2 ) [ 261 ].…”
Section: Potentials Of Antioxidants In Treating Parkinson’s Diseasmentioning
confidence: 99%
“…It also mitigates the reduction of DA in striatum of rotenone-treated rats [ 259 ]. However, a population-based study does not find the relationship between pioglitazone use and PD incidence among diabetic patients [ 260 ]. A randomized, double-blind, placebo-controlled trial of pioglitazone (15 or 45 mg/day) on 210 PD patients could not show a difference of UPDRS scores between treatment and placebo groups ( Table 2 ) [ 261 ].…”
Section: Potentials Of Antioxidants In Treating Parkinson’s Diseasmentioning
confidence: 99%
“…One study was excluded because of failure to be related to the incidence of PD. Ultimately, the remaining five qualified studies [913] involving 347,556 patients were considered suitable for this meta-analysis. The Kappa for agreement between the two independent investigators was 0.8.…”
Section: Resultsmentioning
confidence: 99%
“…Three [9,10,12] studies showed that TZDs use was associated with a reduced incidence of PD, whereas the other 2 [11,13] studies did not find such association. Pooled analysis of the 5 included studies showed that the OR was statistically significant (OR, 0.70; 95% CI, 0.51 to 0.96; p = 0.03; Fig 2A), in spite of obvious heterogeneity (Chi 2 , 28.25; I 2 = 86%; p < 0.0001; tau 2 = 0.10), indicating that the use of TZDs was associated with significantly reduced risk of PD in diabetic patients with TZDs treatment compared with those without.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the use of coenzyme Q10, a potent antioxidant, failed to demonstrate an improvement in clinical trials [40]. Neither pioglitazone [41,42] nor genomic strategies to increase neurturin (AAV-mediated gene therapy) succeeded in the clinical trials [43,44], since disease-modifying activity was not demonstrated.…”
Section: Therapeutic Strategies For Parkinson's Diseasementioning
confidence: 99%